Enema versus polyethylene glycol for the management of rectal faecal impaction in children with constipation – a systematic review of randomised controlled trials - Dziechciarz, Piotr; Wojtyniak, Katarzyna; Horvath, Andrea; Szajewska, Hanna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction: Rectal faecal impaction (RFI) from functional constipation is a common problem in children. Maintenance therapy should start after successful disimpaction. However, there is uncertainty with regard to the optimal disimpaction regimen. Aim: We systematically evaluated the effect of polyethylene glycol (PEG) compared to enema for treating RFI. Material and methods: The MEDLINE, EMBASE, and the Cochrane Library, with no language restrictions, were searched up to July 2014 for randomised controlled trials (RCTs) evaluating the effect of PEG compared with enema for disimpaction in children with functional constipation. The risk of bias was assessed using the Cochrane risk of bias tool. Results: Two RCTs, involving 170 children aged 1 to 17 years, met the inclusion criteria. The studies were generally low in methodological quality. Compared with the enema group, the PEG 3350 group had significantly reduced chance for treatment success, but the difference was of a borderline statistical significance (RR = 0.83, 95% CI: 0.7–0.99). The use of PEG was also more likely to increase defecation frequency, but increased the risk of watery stools and increased faecal incontinence. Other outcomes, in general, were similar in both groups. Conclusions: Current evidence does not allow us to conclude which intervention is more effective for treating RFI in children with functional constipation. These results should be interpreted with caution due to the limited number of trials and the low quality of reporting in these trials, high or unknown risk of bias, and sparse data. Further high-quality, adequately powered RCTs are needed to determine the optimal management.